STUDY THE QUALITY OF SMALL SHRIMP (Aceteserythraeus) SURIMI WITH THE ADDIITON OF DIFFERENT PROTECTANT - Kiki Aliandi Siregar; Suparmi Suparmi; Dewita Buchari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The purpose of this research is to determine the effect of the addition of different protectant to the quality of small shrimp surimi. The method used in this research is experimental method with Completely Randomized Design (CRD) non factorial with addition of different protectant which consists of 3 levels of treatment, i.e. (without addition protectant)2(4% Sukrosa), and S3(4% Sorbitol). Based on organoleptic test, chemical analysis, and fold test of small shrimp surimi with different protectant addition, it isobtained that the best treatment is S3(4% Sorbitol). The characteristics of small shrimp surimi for appearance is flat, neat, gray colour and very smooth preferred by 11 panelists  (44%), the specific aroma of small shrimp surimi (6.84) preferred by 10 panelists (40%), compact, solid and very elastic texture (7.32) preferred 10 panelists (40%). Meanwhilewater, protein, fat, ash content, and folding test are 71.62%, 17.58%, 3.56%, 23.69%, and 2.00, respectively Keywords : Protectant,small shrimp, surimi